Traditional Massage-Induced Iliotibial Band Syndrome: A Case Report - Nugroho, Nunung; Andriani, Bernadheta Ayu (Surabaya Physical Medicine and Rehabilitation Journal, 2024)
Iliotibial Band (ITB) Syndrome is common among athletes, such as runners and cyclists. There are several theories regarding the etiology of ITB Syndrome, including friction, compression, and chronic inflammation. We report a rare case of ITB Syndrome induced by traditional massage after a history of chronic knee pain. A 63-year-old female visited our Pysical Medicine and Rehabilitation Department with the pain of the lateral side of the right knee for four months after traditional massage. The physical examination showed a positive Ober test and Noble compression test. We performed an ultrasonography on the lateral right knee and found fluid effusion beneath the ITB confirming the diagnosis of ITB Syndrome. A pain intervention was performed with ultrasound-guided aspiration and injection of steroid beneath the ITB. After the procedure and rehabilitation program of cryotherapy and ultrasound therapy, the pain was reduced greatly and there was no need for further management.